Estudo dos gargalos em licitações de um município paulista, à luz da gestão por processos e da teoria das restrições: análise e proposições de melhorias - Camargo, Maria Emília Silveira (2020)
Government procurement moves an important part of the budgets of the federal entities, therefore, the good management of the bidding procedures is essential to avoid the misuse of public resources, requiring from public managers the capacity to instruct the processes and speed up their conduct. The Auction, a bidding modality regulated by Federal Law No. 10,520 / 2002, intended exclusively for the acquisition of goods and the contracting of common services,with performance and quality standards, objectively defined in the Notice, by means of usual specifications in the market, it is used with great frequency by Organs public agencies, for conferring to the competitions, greater speed, economy, competitiveness and advantage in the proposals. Considering thatthe Municipality of Itapeva, carried out in the period from 2011 to 2018, approximately 64% of its purchases through the use of Presentials, this work has as object this type of processes, since it is on these that the highest charges fall for results andspeed in processing. In this way, this research has as its general objective -to identify opportunities for improvements to remedy / correct the critical factors in the bottleneck units, which compromisethe speed and quality of the instruction of the bidding processes of the On-Site Auction, triggered for the acquisition of common goods and services in the municipality of Itapeva / SP. The research classified as applied, descriptive and qualitative, was outlined as a single Case Study, having as its locus of research the Municipality of Itapeva / SP and the activities developed by the Department of Materials and Supplies and other public departments responsible for processing the bidding processes, thus, it proposes the combined application of the ProcessManagement Methodology or Business Process Management -BPM approach and the Theory of Constraints, as tools for continuous improvement. Based on the application of the tools, the current situation was mapped -“As is” mapping of the processes and the verification of the execution times of the activities that make up the procedure and the format of the procedural instruction, through the collection of documentary data and semi-structured interviews. As a result of the research, 11 (eleven) improvement proposals were elaborated, to be applied in the bottleneck environment, the Department of Materials and Supplies, in order to facilitate the progress of the works performed by the sector, giving greater speed and quality to the bidding procedures. With the realization of the research it was possible to verify the contributions of the application of the approaches to the bidding processes, which may be implemented by the Municipality of Itapeva, as well as by other federal entities, in the investigated bidding modality, as well as in the other bidding modalities defined in the federal legislation, including, in other types of administrative processes, making public actions more transparent, establishing flows andstandardizing procedures.